"Norvegia" Antarctic Expedition of 1929-1930 : Commander H. Riiser-Larsen in command / copyright . by the American Geographical Society of New York - American Geographical Society of New York (American Geographical Society of New York, 1930)
Depths shown by soundings in meters and isolines. Includes 2 inset maps. "The Geographical Review, Vol. XX, No. 4, 1930, Plate VII" -- upper right margin. Color 1:25,000,000